Depression mediates motor dysfunction’s effect on sleep quality in ALS: a mediation analysis study - Zhu, Yuchen; Zhang, Gan; Liu, Hong; Yin, Tielun; Zhang, Jiaying; Yang, Yanjing; Bai, Linna; Liu, Xiaoxuan; Fan, Dongsheng; Ye, Shan (Frontiers in Neuroscience, 2026)
IntroductionPoor sleep quality affects 50–63% of Amyotrophic lateral sclerosis (ALS) patients, exacerbating disease burden and reducing quality of life. This study aimed to investigate the relationships among disease severity, depressive symptoms, and sleep quality in ALS, with a focus on the mediating effects of depression.MethodsOur study enrolled 408 ALS patients. Disease severity was assessed using the ALS Functional Rating Scale-Revised (ALSFRS-R), sleep quality via the Pittsburgh Sleep Quality Index (PSQI), and psychological status using the Hamilton Depression (HAMD) and Anxiety (HAMA) scales. Statistical analyses included Spearman correlations, multivariate regression, and mediation analysis (Hayes’ PROCESS macro).ResultsPoor sleep quality (PSQI > 5) was observed in 54.4% of patients. Multivariate analysis found ALSFRS-R (β = −0.135, p = 0.042) and HAMD (β = 0.270, p < 0.001) correlated with sleep quality. Initial mediation analysis using the full ALSFRS-R and PSQI scales was not significant. Aimed to further explore the correlation, we derived specific subscales ALSFRS-R’ (motor/respiratory components) and PSQI’ (sleep efficiency/ daytime dysfunction), which more correlated with each other. Mediation analysis of these subscales revealed that depressive symptoms accounted for 36.3% of the indirect effect between ALSFRS-R’ and PSQI’.DiscussionOur cross-sectional exploratory study suggests that depression may partly mediate the relationship between motor dysfunction and poor sleep quality in patients with ALS. Although our mediation analysis suggested a potential association, further longitudinal cohort studies are needed to confirm these findings. The potential mediating role of depression underscores the need for an integrated clinical management approach addressing not only motor symptoms but psychological well-being as well.